2021
DOI: 10.3390/genes12050666
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Genetic Potential of the Peregrine Falcon (Falco peregrinus peregrinus) Population Used in the Reintroduction Program in Poland

Abstract: Microsatellite DNA analysis is a powerful tool for assessing population genetics. The main aim of this study was to assess the genetic potential of the peregrine falcon population covered by the restitution program. We characterized individuals from breeders that set their birds for release into the wild and birds that have been reintroduced in previous years. This was done using a well-known microsatellite panel designed for the peregrine falcon containing 10 markers. We calculated the genetic distance betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…Compared to our previous study, which included both breeding and wild falcons [ 20 ], the number of observed alleles for two markers was lower (NVHfp107, NVHfp92_1) and for three was higher (NVHfp5, NVHfp54, NVHfp82_2). The effective number of alleles was lower for two markers (NVHfp13, NVHfp5) and higher for the other seven.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Compared to our previous study, which included both breeding and wild falcons [ 20 ], the number of observed alleles for two markers was lower (NVHfp107, NVHfp92_1) and for three was higher (NVHfp5, NVHfp54, NVHfp82_2). The effective number of alleles was lower for two markers (NVHfp13, NVHfp5) and higher for the other seven.…”
Section: Discussioncontrasting
confidence: 76%
“…These markers were characterized by the presence of high locus polymorphism, primer melting points and product length, which allowed the reactions to be carried out as one multiplex PCR (polymerase chain reaction) procedure. Reactions were performed as described by Puchała et al [ 20 ]. Marker NVHfp79-4 was excluded from analysis due to null heterozygosity and low variability.…”
Section: Methodsmentioning
confidence: 99%